Low Cost Heart Rate Monitor Using Led-Led Sensor - Ahmed Mahrous Ragib (Al-Khwarizmi College of Engineering – University of Baghdad, 2009)
A high sensitivity, low power and low cost sensor has been developed for photoplethysmography (PPG) measurement. The PPG principle was applied to follow the dilatation and contraction of skin blood vessels during the cardiac cycle. A standard light emitting diodes (LEDs) has been used as a light emitter and detector, and in order to reduce the space, cost and power, the classical analogue-to-digital converters (ADCs) replaced by the pulse-based signal conversion techniques. A general purpose microcontroller has been used for the implementation of measurement protocol. The proposed approach leads to better spectral sensitivity, increased resolution, reduction in cost, dimensions and power consumption. The basic sensing configuration presented is capable of detecting the PPG signal from a finger or toe, and it is very simple to extract the heart rate and heart rate variability from such a signal.